2016
DOI: 10.1039/c6cp03789e
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the cryptic role of a catalytic electron in a photochemical bond dissociation using excited state aromaticity markers

Abstract: The breaking of bonds by catalytic electrons has gained prominence very recently but has been limited to cases where electrons from external sources have been used. Here, we show that upon photoexcitation, an electron of intramolecular origin is transferred from one part of a molecule to another followed by bond cleavage and then returns to its original moiety on completion of its catalytic function. By a proper assessment of the dramatic changes in aromaticity in excited-state intermediates along the photorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Cao (2018) also investigated the role of ring puckering and ring opening in the photorelaxation of thiazole and isothiazole using a modified SHARC-MOLPRO interface. Banerjee, Halder, Ganguly, and Paul (2016) studied the electron-catalyzed photofragmentation of 5-phenyl-2H-tetrazole, in which upon photoexcitation, an electron is injected from one part of the molecule into another part, where bond dissociation takes place, and afterward the electron returns to its originating part of the molecule. Bellshaw et al (2017) showed that the dynamics of the CS 2 molecule is strongly affected by SOCs, as the dissociation barrier is much smaller in the triplet states than in the singlet ones.…”
Section: Sharc Application Examplesmentioning
confidence: 99%
“…Cao (2018) also investigated the role of ring puckering and ring opening in the photorelaxation of thiazole and isothiazole using a modified SHARC-MOLPRO interface. Banerjee, Halder, Ganguly, and Paul (2016) studied the electron-catalyzed photofragmentation of 5-phenyl-2H-tetrazole, in which upon photoexcitation, an electron is injected from one part of the molecule into another part, where bond dissociation takes place, and afterward the electron returns to its originating part of the molecule. Bellshaw et al (2017) showed that the dynamics of the CS 2 molecule is strongly affected by SOCs, as the dissociation barrier is much smaller in the triplet states than in the singlet ones.…”
Section: Sharc Application Examplesmentioning
confidence: 99%
“… 10 This triggered a renewed interest in excited-state aromaticity (ESA), both in terms of obtaining spectroscopic evidence for the concept 11 14 and applying it to the design of novel synthetic protocols. 15 17 Furthermore, this trend led to the discovery of ways of tuning ESA through steric and electronic substituent effects 18 and to the development of strategies for using ESA to modulate double-bond photoisomerization, 19 22 proton-transfer, 21 , 23 25 electrocyclization, 26 conformational-planarization, 27 29 and photodissociation 30 reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, intramolecular charge transfer of an electron from an excited state antiaromatic benzene ring was recently found to occur during photodissociation of a protecting group. 39,40 Now, how does the aromaticity of 2 change upon photoexcitation and subsequent ionization to the radical cation? We investigated this with calculations on the model compound 2'.…”
Section: Excited State Antiaromaticity As a Potential Driving Force Fmentioning
confidence: 99%